Spastic Paraparesis in Young Men With Spinal Meningioma and Spinal Arteriovenous Malformation: A Case Report - Leonard Christianto Singjie; Ivan Jeremia; Esdras Ardi Pramudita (Universitas Airlangga, 2021)
Background: Compared to trauma cases, the publication of non-traumatic events is much less, although the incidence is estimated to be as much as a traumatic event. This case report presents spinal cord tumors together with arteriovenous malformation (AVM) in young men, where there are no previous case reports that the authors can find.Case Report: A 22-year-old male patient with complaints of pain in the back (NPRS 8-9), followed by difficulty moving the lower limb accompanied by a burning sensation, problem in defecation, and urination. We found motor weakness in the lower extremities (1/1), positive pathological reflexes, and sensibility disorders on physical examination.Discussion: According to history taking, physical examination, and MR Imaging, the spastic paraparesis symptom in this patient is likely due to a spinal cord tumor, which is meningioma (according to histopathological examination). Where back pain rarely presents in the patient with spinal AVM. Laminectomy and tumor destruction were the gold standards of therapy, and the symptom was relieved.Conclusion: A complete examination is the main key in determining the appropriate therapy for the patient's disease. In this case, the manifestation of spastic paraparesis was likely to be caused by meningioma rather than spinal AVM. Laminectomy and extirpation of the spinal meningioma were done as the gold standard of therapy, and the symptom was relieved. In contrast, spinal AVM was not performedÂ and is still under observation.